Surah Al-Insan Ayat 1-2 dalam Lensa Tafsir Klasik dan Kotemporer - Udi Yuliarto; Hepni Putra; Ica Fauziah Husnaini; Muhafizah (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
The holy Qur'an, as the main source of teachings in Islam, has a central role in guiding humanity in every aspect of life. One of its suras, Al-Insan, offers an in-depth look at the nature of human existence and its relationship with the Creator. This article explores the meaning of the verses of surah Al-Insan by taking the perspectives of classical and contemporary commentaries, namely tafsir Ibn Katsir and tafsir Al-Misbah. Through a qualitative approach, this research presents analyses that are rich in nuances and reveal new dimensions in understanding the meaning of the Qur'anic verses. The results of this study present an in-depth description of the meaning of the verses of surah Al-Insan with the aim of making it easier to understand the essence of the Qur'anic message in the present context. The findings show that each tafsir, both classical and contemporary, provides unique insights that are relevant to the times and strengthen the understanding of the values contained in the Qur'an.